Fundamental Studies of Soot Formation and Diagnostic Development in Nonpremixed Combustion Environments - Bennett, Anthony (KAUST Research Repository, 2020)
Abstract: Soot from combustion emissions has a negative impact on human health and the environment. Understanding and controlling soot formation is desirable to reduce this negative impact, especially as energy demands continue to increase. In this work, a range of fundamental combustion experiments are performed to better understand the soot formation process, and to develop diagnostics for measuring soot properties.

First, studies on the effects of doping the flame with different polycyclic aromatic hydrocarbons (PAHs) was performed to investigate soot nucleation mechanisms. Soot formation was found to be most sensitive to phenylacetylene addition and nucleation through physical dimerization appears to be unlikely. Next, the effects of ammonia addition, a possible future fuel, on soot formation in laminar nonpremixed ethylene counterflow flames was performed. A reduction in soot volume fraction was observed and attributed to chemical effects of ammonia addition.

Second, the investigation and development of several types of diagnostics was performed. Soot is typically reported to scale with pressure as Pn where P is pressure and n is a scaling factor. A wide range of scaling factors for ethylene coflow flames have been reported using different types of diagnostics. In this work, a comparison between a light extinction technique and PLII was performed and differences between reported values was explored. Next, the time resolved laser induced incandescence (TiRe-LII) diagnostic was advanced by exploring the effects of SVF on local gas heating. Errors introduced into this model by neglecting local gas heating are explored. Finally, a new diagnostic was developed for 3 dimensional measurements of SVF and velocity in turbulent flames using a technique known as diffuse-backlight illumination extinction imaging.

Third, the application of gated 2D TiRe-LII was assessed in pressurized environments on laminar coflow flames. Comparisons between TiRe-LII and thermophoretically captured soot imaged by transmission electron microscopy (TEM) was performed. TiRe-LII was found to have reasonable agreement with TEM measurements if the SNR was high, but due to the large disparity in primary particle size in pressurized environments errors in 2D TiRe-LII can be significant.